136 NOVA primary results randomised controlled study of natalizumab Q6W versus continued Q4W treatment for MS. Issue 9 (12th August 2022) - Foley, John; Defer, Gilles; Ryerson, Lana Zhovtis; Cohen, Jeffrey; Arnold, Douglas; Butzkueven, Helmut; Cutter, Gary; Giovannoni, Gavin; Killestein, Joep
Abstract : Background: Natalizumab every-6-week (Q6W) dosing is associated with lower progressive multifocal leukoencephalopathy risk than every-4-week dosing (Q4W) in retrospective analyses. NOVA is the first randomised trial to assess Q6W efficacy. Objective: Evaluate natalizumab Q6W efficacy in patients previously treated with natalizumab Q4W for ≥12 months compared with continuation of Q4W over 72 weeks. Methods: NOVA is a randomised, controlled, open-label, rater-blinded phase 3b trial. Included patients were treated with natalizumab Q4W without relapse for ≥12 months. Patients were randomised 1:1 to Q4W (n=248) or Q6W (n=251). The primary endpoint was new/newly enlarging T2 (N/NET2) lesions. Secondary endpoints included clinical and safety outcomes. Results: Proportions of patients with N/NET2 lesions were low in both arms (Q4W:4.1%; Q6W:4.3%). Differ- ences in mean N/NET2 lesions for Q4W and Q6W (primary estimand: 0.05 vs 0.20 [P=0.0755]; secondary estimand: 0.06 vs 0.31 [P=0.0437]) were driven by two Q6W patients with extreme (≥25) values. Secondary outcomes were similar for Q4W and Q6W. Conclusions: Overall, NOVA data suggest most patients stable on natalizumab Q4W can switch to Q6W without clinically meaningful loss of efficacy. Support: Biogen. Disclosures on poster.